Mechanisms of interaction between arsenian pyrite and aqueous arsenite under anoxic and oxic conditions. (1st May 2018) - Qiu, Guohong; Gao, Tianyu; Hong, Jun; Luo, Yao; Liu, Lihu; Tan, Wenfeng; Liu, Fan
Graphical abstract: Arsenian pyrite adsorbs and oxidizes As(III) due to the formation of reactive OH and H2 O2 through the decomposition of water induced by surface Fe(III)–S. The presence of oxygen significantly accelerates oxidation rate of arsenian pyrite. Arsenic release ratio decreases with increasing arsenic content in pyrite during the interaction processes. Highlights: As(III) is mainly adsorbed on the surface of arsenian pyrite. As(III) oxidation rate increases with increasing arsenic content in pyrite. OH and H2 O2 are produced on the surface of arsenian pyrite. The oxidation of dissolved As(III) and arsenian pyrite increases in air. Arsenic release ratio decreases with increasing arsenic content in pyrite. Abstract: Pyrite affects the conversion and migration processes of arsenic in soils and waters. Adsorption and redox reactions of arsenite (As(III)) occur on the surface of pyrite, and the interaction processes are influenced by the arsenic incorporated into pyrite. This work examined the effects of arsenic content, pH and oxygen on the interaction between arsenian pyrite and aqueous As(III) and investigated the underlying mechanisms. The results indicated that arsenic incorporation led to a high content of Fe(III) in pyrite, and that As(III) was mainly adsorbed on pyrite surface and part of As(III) was oxidized to As(V) by the newly formed intermediates including hydroxyl radicals and hydrogen peroxide. The oxidation rate increased with increasing arsenic content in the pyrite and the presence of air (oxygen), and first decreased and then increased with increasing pH from 3.0 to 11.0. Hydroxyl radicals and hydrogen peroxide significantly contributed to the oxidation of pyrite and aqueous As(III) in acidic and alkaline solutions, respectively. Although pyrite oxidation increased with increasing arsenic content as indicated by the elevated concentrations of elemental S and SO4 2−, the percentage of released arsenic in total arsenic of the arsenian pyrite decreased due to the adsorption of arsenic on the surface of newly formed ferric (hydr)oxides, especially the ferric arsenate precipitate formed in high pH solutions. The present study enables a better understanding of the important interaction process of dissolved arsenite and natural pyrites in the study of groundwater contamination, arsenic migration/sequestration, and acid mine drainage formation.